Student's Perspective on of Google Classroom in Biology Learning: A Study on National Standards of Education (FMIPA UNNES, 2023)
This study aims to obtain an overview of students' perspectives on the use of Google Classroom in Biology learning in schools in terms of the National Education Standards (SNP). The sample in this study was randomly selected as many as 86 high school students in East OKU Regency. The instrument used was a questionnaire containing 33 statements developed from three aspects of the SNP, namely Process Standards, Facilities and Infrastructure Standards, and Assessment Standards. The three SNPs studied were described in the indicators. Questionnaires were distributed with the help of Google Forms. The research data were then analyzed by calculating the percentage of each indicator in each aspect of the SNP being studied. The results of this study indicate that the use of Google Classroom in Biology Learning for the three aspects of SNP is in the good category. The Assessment Standard is the Standard with the highest achievement (85.40%) while the Facilities and Infrastructure Standard is the Standard with the lowest achievement (54.46%). The results of this study indicate that it is important to improve facilities and infrastructure before online learning is carried out using Google Classroom in Biology learning at school.